Model of Sekolah Penggerak in Building Accelerated Transformation of Jambi University Partner Schools - Ahmad Hariandi; Muhammad Sholeh (Jurnal Penelitian Pendidikan IPA, 2023)
This research is based on the Sekolah Penggerak model in the development of accelerated school transformation from the implementation of the Sekolah Penggerak program at partner schools at Jambi University. From the results of the initial grand tour, it can be seen that the partner school learning environment still contains bullying and disruption, as well as learning that is not yet student-centered. The research results show that the main elements of the Sekolah Penggerak model in developing accelerated school transformation are leadership development, which is the driving force in the governance system, improving the quality of communication, improving the quality of teachers, and problem-solving. These elements can improve the stages of school transformation at level 3, namely the expected stage, where bullying rarely occurs, and teachers carry out learning according to needs. The synergy of elements in increasing the stages of school transformation leads to the implementation of the School Mobilization Program, namely accelerating school transformation, improving the quality of education, increasing the competence of school principals and teachers, and accelerating the implementation of digitalization in schools. And open up opportunities to become a transformation catalyst for other schools